Disability, Health and Human Development 2017
DOI: 10.1057/978-1-137-53638-9_2
|View full text |Cite
|
Sign up to set email alerts
|

The Human Development Model of Disability, Health and Wellbeing

Abstract: This chapter sets the conceptual framework for the book. It introduces a new model, the human development model of disability, health and wellbeing, based on Amartya Sen's capability approach. Disability is defined as a deprivation in terms of functioning and/or capability among persons with health conditions and/or impairments. The human development model highlights in relation to wellbeing the roles of resources, conversion functions, agency, and it uses capabilities and/or functionings as metric for wellbei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 40 publications
0
21
0
Order By: Relevance
“…As Mont [24] highlights discussions about how to "count" disability often imply that populations can be cleanly divided into people with disabilities and people without disabilities, using a pre-specified cut-off. In fact, disability, from the perspective of functional ability, is better understood as operating on continuum [25,26]. That is, the functional ability of every person varies and whether this constitutes "disability" first depends on the context that disability is being assessed in.…”
Section: The Importance Of How Data Is Countedmentioning
confidence: 99%
“…As Mont [24] highlights discussions about how to "count" disability often imply that populations can be cleanly divided into people with disabilities and people without disabilities, using a pre-specified cut-off. In fact, disability, from the perspective of functional ability, is better understood as operating on continuum [25,26]. That is, the functional ability of every person varies and whether this constitutes "disability" first depends on the context that disability is being assessed in.…”
Section: The Importance Of How Data Is Countedmentioning
confidence: 99%
“…The lack of difference between men and women with disabilities stands somewhat in contrast to evidence from studies in other locations, where differences between men and women with disabilities are more apparent. For example, school attendance and attainment is often found to be lower amongst girls with disabilities compared to boys with disabilities [37,38], as is employment for women with disabilities compared to men with disabilities [30,33,37]. The lack of association in this study may reflect limitations of the study's power, as some of the observed differences were close to statistical significance (e.g., employment), or differences in the socio-cultural context of the Maldives compared to other study settings.…”
Section: Discussionmentioning
confidence: 99%
“…Around the world, and when using every measure of poverty, people with disabilities are more likely to live with poverty [10]. While traditional indicators suggest income is the most significant for understanding poverty, more recent multi-dimensional poverty indicators, including education, employment, food security, health among others, recognize greater complexity of poverty and that different aspects of poverty may be different in varying countries [11,12].…”
Section: Introductionmentioning
confidence: 99%